(untitled) (Southwestern Research Journal, 2023)
This study attempts to explore the impacts of labour influx related to road construction in Nepal with particular attention to the local community. The study is based on consultation and focus group discussions with laborers and people living in local communities that hosted the project and additional key informant interviews with road project staffs, local leaders of major political parties, schoolteachers, local service providers such as police officers, medical workers, and others. The study concludes that influx of laborers have both positive and negative impacts on local community. Adequate monitoring and adaptive management of likely adverse impacts from labor influx are keys to properly addressing them and mitigating risks. This study identifies the way forward and instruments to prepare and implement in reducing labor influx for preventing the threats of human security of local community along the road alignment.